2017
DOI: 10.1007/s11538-017-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Binets: Fundamental Building Blocks for Phylogenetic Networks

Abstract: Phylogenetic networks are a generalization of evolutionary trees that are used by biologists to represent the evolution of organisms which have undergone reticulate evolution. Essentially, a phylogenetic network is a directed acyclic graph having a unique root in which the leaves are labelled by a given set of species. Recently, some approaches have been developed to construct phylogenetic networks from collections of networks on 2- and 3-leaved networks, which are known as binets and trinets, respectively. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…. , 1 do Subdivide the incoming edge of xi with a node px; 8 Subdivide the incoming edge of yi with a node py; 9 Add the edge pypx to N ; Subdivide the incoming edge of yi with a node py; 12 Add a new node labelled xi to N ; 13 Add the edge pyxi to N ; 14 return N ;…”
Section: Procedures Constructnetworkfromsequence(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…. , 1 do Subdivide the incoming edge of xi with a node px; 8 Subdivide the incoming edge of yi with a node py; 9 Add the edge pypx to N ; Subdivide the incoming edge of yi with a node py; 12 Add a new node labelled xi to N ; 13 Add the edge pyxi to N ; 14 return N ;…”
Section: Procedures Constructnetworkfromsequence(s)mentioning
confidence: 99%
“…Instead of having almost all leaves, the subnetworks can also be allowed to have only few leaves. For example, low level networks can be reconstructed from their full set of binets [5,12], trinets [10,16] or quarnets [4].…”
Section: Introductionmentioning
confidence: 99%
“…Building blocks are generally some class of subnetworks, e.g., binets (van Iersel et al. 2017), trinets (Huber and Moulton 2013), or trees, used to infer the original network. A potential problem here is that there could be more than one network with the same building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…2017; van Iersel et al. 2017). Two of the more prominent network classes are the tree-child networks (Cardona et al.…”
Section: Introductionmentioning
confidence: 99%
“…Partly due to the aforementioned negative deterministic results, recent studies have investigated whether or not rooted phylogenetic networks are determined by their embedded subnetworks like binets [10,14] and trinets [10,12,13], that is, rooted phylogenetic networks on two and three leaves, respectively. It has been shown that trinets determine rooted binary level-two and rooted binary tree-child networks [13].…”
mentioning
confidence: 99%